Regulatory T cells suppress CD4+ T cells through NFAT‐dependent transcriptional mechanisms. (29th July 2014) - Shin, Daniel S; Jordan, Ayana; Basu, Samik; Thomas, Rajan M; Bandyopadhyay, Sanmay; de Zoeten, Edwin F; Wells, Andrew D; Macian, Fernando
Abstract : Regulatory T cells are shown to induce the activation of NFAT1‐dependent gene expression in stimulated T‐helper cells, including the transcription of Ikaros, which is required for optimal T‐helper cell suppression in vitro and in vivo . Abstract: Regulatory T cells (Tregs) control autoreactive T cells by inhibiting activation‐induced proliferation and cytokine expression. The molecular mechanisms responsible for the inactivation of effector T cells by Tregs remain yet to be fully characterized. We report that T‐helper cells stimulated in the presence of Tregs quickly activate NFAT1 and have increased NFAT1‐dependent expression of the transcription repressor Ikaros. NFAT1 deficiency or dominant‐negative Ikaros compromises Treg‐mediated inhibition of T‐helper cells in vitro and in vivo . Thus, our results place NFAT‐dependent mechanisms as general regulators of T‐cell tolerance and show that Treg‐mediated suppression of T‐helper cells results from the activation of NFAT‐regulated gene expression. Synopsis: This study shows that regulatory T cells activate NFAT1‐dependent gene expression in stimulated T‐helper cells, including the transcription of Ikaros, which is required for optimal T‐helper cell suppression in vitro and in vivo . Activation of T‐helper cells in the presence of tTregs induces the NFAT1‐dependent expression if Ikaros, likely as a result of the downmodulation of costimulatory ligands in antigen‐presenting cells. NFAT1‐deficient CD4 + T cells or T cells expressing a dominant‐negative form of Ikaros are resistant to tTreg‐mediated suppression.